Trust in Leader as a Mediator of the Relationship Between Member and Leader Machiavellianism and Work Engagement in Student Organizations - Najwa Haq Filhal; Siti Nuzulia (Journal of Educational, Health and Community Psychology, 2026)
This study examined the mediating role of trust in leader in the relationship between leader and member Machiavellianism and work engagement within student organizations. A cross-sectional correlational survey design was employed involving 150 students actively engaged in organizational activities. Data were collected using the MACH-IV Scale, the Trust in Leader Scale, and the Utrecht Work Engagement Scale (UWES-9). The hypotheses were tested using General Linear Model mediation analysis. The findings revealed that trust in leader was positively associated with work engagement (B = 0.25857, p < .001). Mediation analysis further demonstrated that leader Machiavellianism exerted a significant negative indirect effect on work engagement through trust in leader (B = -0.153, 95% CI [-0.2859, -0.0209]). Interestingly, member Machiavellianism showed a significant positive direct effect on work engagement (B = 0.30167, p < .001). These findings underscore the critical role of trust in leadership in fostering organizational engagement. At the same time, the results suggest that highly Machiavellian members may remain actively engaged for instrumental or strategic purposes. This study contributes to the emerging literature on dark personality traits and organizational behavior by highlighting the complex dynamics between leadership trust, Machiavellian tendencies, and engagement in student organizational contexts.